Caffeine and Sugars Interact in Aqueous Solutions: A Simulation and NMR Study - Tavagnacco, Letizia (2012)
Molecular dynamics simulations were carried out on several systems of caffeine interacting with simple sugars. These included a single caffeine molecule in a 3 molal solution of α-D-glucopyranose, at a caffeine concentration of 0.083 molal; a single caffeine in a 3 molal solution of β-D-glucopyranose, and a single caffeine molecule in a 1.08 molal solution of sucrose (table sugar). Parallel Nuclear Magnetic Resonance titration experiments were carried out on the same solutions under similar conditions. Consistent with previous thermodynamic experiments, the sugars were found to have an affinity for the caffeine molecules in both the simulations and experiments, and that the binding in these complexes occurs by face-to-face stacking of the hydrophobic triad of protons of the pyranose rings against the caffeine face, rather than by hydrogen bonding. For the disaccharide, the binding occurs via stacking of the glucose ring against the caffeine, with a lesser affinity for the fructose observed. These findings are consistent with the association being driven by hydrophobic hydration, and are similar to the previously observed binding of glucose rings to various other planar molecules, including indole, serotonin, and phenol.